Cyberostracism and knowledge sharing: The mediating role of social anxiety in e-learning environments - AKÇAY, Arif; KAYİŞ, Ahmet Rıfat (Journal of Educational Technology and Online Learning, 2023)
Ostracized individuals face a series of negative situations and feel social anxiety during their interactions with others. However, individuals with social anxiety may not share their knowledge because of the discomfort they experience in interactions. The aim of this study is to examine the mediating role of social anxiety in learner–learner interaction in terms of the relationship between cyberostracism and knowledge sharing in e-learning environments. A total of 268 pre-service teachers participated in the study. The study determined the relationship between the variables with Pearson’s correlation coefficients and used a regression-based mediation test to examine the mediator model. It found that cyberostracism was positively related to social anxiety in learner–learner interactions in e-learning environments and negatively associated with knowledge sharing. There was also a negative relationship between social anxiety and knowledge sharing. Moreover, cyberostracism predicted knowledge sharing in e-learning environments. Finally, we determined that social anxiety in learner–learner interactions was the full mediator in the relationship between cyberostracism and knowledge sharing. Therefore, it can be argued that cyberostracism is not a direct predictor of pre-service teachers’ knowledge sharing behavior in e-learning environments and pre-service teachers avoid knowledge sharing due to social anxiety caused by cyberostracism. The research results also led to suggestions for practice and research.
Keywords: Eğitim Üzerine Çalışmalar; Cooperative/collaborative learning; E-learning; Knowledge Sharing; Cyberostracism; Social Anxiety; Studies on Education; 4. Education